Performance Enhancement of Transparent Amorphous IGZO Thin-Film Transistor Realized by Sputtered Amorphous AlOx Passivation Layer. (20th April 2021) - Li, Yuanbo; Sun, Jianxun; Salim, Teddy; Liu, Rongyue; Chen, Tupei
Abstract : We report a high-mobility transparent Indium-Gallium-Zinc-Oxide (IGZO) thin-film transistor (TFT) with sputtered AlOx passivation layer. The interfacial region between the IGZO layer and the AlOx layer played a crucial role in improving the field-effect mobility (the maximum field-effect mobility increased from 6.292 cm 2 Vs −1 for the TFT without the AlOx layer to 69.01 cm 2 Vs −1 for the TFT with the passivation layer) and the on/off current ratio (from ∼10 7 without the layer to ∼10 8 with the layer). The driving current of IGZO TFT was also significantly enhanced. The formation of the interfacial layer has been investigated and verified. The ion bombardment during the AlOx deposition broke the In-O bond in IGZO, generating oxygen ions (O 2− ). The segregation of the O 2− was facilitated by the sputtered amorphous AlOx . A metallic In-rich layer with high oxygen vacancy concentration was formed at the interface, leading to an increase in the carrier concentration in the interfacial layer. Besides the electrical performance, the reliability tests, including long-term exposure in the ambient environment and positive bias illumination stress (PBIS), showed improved results as well.